EZgate - A ﬂexible Gateway for the Internet of Things - Teubler, Torsten; Walther, Ulrich; Hellbrück, Horst (Electronic Communications of the EASST, 2011)
Two years ago a survey of the wireless world research forum predicted that in the year 2017 there will be seven trillion wireless devices for seven billion humans which is equivalent to 1000 devices per human being on the average. The future will show if this incredible number will be reached but for sure we will see an increasing number of wireless devices forming the Internet of the future. The new evolving “Internet of Things” is one of the challenging research topics today. With many wireless resource constraints devices, smart gateways integrating these small battery-powered devices into the future Internet will play a major role for the success of the Internet of Things. These gateways will work as a communication endpoint or proxy enabling transparent services including mechanisms for seman- tic service discovery, Quality of Service (QoS), and performance enhancing prox- ies (PEPs). In this work we will introduce a fully operable TCP/IP-Stack EZgate written in Java that allows designing and implementing such gateways for wireless networks in a ﬂexible and fast approach and compare it with related work. We will demonstrate how the protocols in this stack can be assembled in a ﬂexible manner, creating various types of gateways and can be easily extended to implement cross layer techniques. Finally, we evaluate the performance of the implementation for delay and throughput performance to show that EZgate is suitable for use in a pro- ductive environment.